Decision making in pressured competition situation: A study from the field of elite sports - Foong, P. L. C. (5th International Seminar on Sports and Exercise Psychology 2018 .Official Conference Proceeding, 2018)
"The more confidence you can give them in leading the team, in making decisions on the field, the better they`re gonna play. Also it makes them feel good, it`s good for their self-esteem." This was an insightful statement highlighted by Graham Henry, the head coach of the all-conquering New Zealand All Blacks Rugby team (Paul, 2012; SkyTV). The interactive and continuous nature of team sports require athletes to switch between attack and defense numerous times during a game, concentrate on the designated roles essential for their playing position and the team game plan (Hodge, Lonsdale, & McKenzie, 2005). Athletes are required to make tactical decisions on the move during pressured situation in the game without direct support from coaches, therefore the importance of optimal in-game decision-making becomes paramount (Hodge et al., 2005). In this presentation, the effectiveness and impact in administering electronic applications in training, which are an electronic version of the concentration grid exercise and the Flip Flop Reflex Tester, are being highlighted. Besides acknowledging the properties in enhancing concentration, the emphasis on identifying the athletes' competency in reaction time, handling distraction, performing under pressure, goal settings and predicting performance provided an insight into the developmental process of enhancing decision making in competitive situation of elite sports settings.